Readmissions, Postdischarge Mortality, and Sustained Recovery Among Patients Admitted to Hospital With Coronavirus Disease 2019 (COVID-19). (20th August 2022) - Moestrup, Kasper S; Reekie, Joanne; Zucco, Adrian G; Jensen, Tomas Ø; Jensen, Jens-Ulrik S; Wiese, Lothar; Ostrowski, Sisse R; Niemann, Carsten U; MacPherson, Cameron; Lundgren, Jens; Helleberg, Marie
Abstract: Background: Many interventional in-patient coronavirus disease 2019 (COVID-19) trials assess primary outcomes through day 28 post-randomization. Since a proportion of patients experience protracted disease or relapse, such follow-up period may not fully capture the course of the disease, even when randomization occurs a few days after hospitalization. Methods: Among adults hospitalized with COVID-19 in eastern Denmark from 18 March 2020–12 January 2021 we assessed all-cause mortality, recovery, and sustained recovery 90 days after admission, and readmission and all-cause mortality 90 days after discharge. Recovery was defined as hospital discharge and sustained recovery as recovery and alive without readmissions for 14 consecutive days. Results: Among 3386 patients included in the study, 2796 (82.6%) reached recovery and 2600 (77.0%) achieved sustained recovery. Of those discharged from hospital, 556 (19.9%) were readmitted and 289 (10.3%) died. Overall, the median time to recovery was 6 days (interquartile range [IQR]: 3–10), and 19 days (IQR: 11–33) among patients in intensive care in the first 2 days of admission. Conclusions: Postdischarge readmission and mortality rates were substantial. Therefore, sustained recovery should be favored to recovery outcomes in clinical COVID-19 trials. A 28-day follow-up period may be too short for the critically ill. Abstract : The rates of readmissions and deaths after hospital discharge in COVID-19 patients were substantial, favoring the use of sustained recovery as outcome. A 28-day follow-up for recovery outcomes in clinical trials seems too short for critically ill COVID-19 patients.